Drivers of research outcomes in developing countries: The case of Lebanon - Pierre Boutros; Ali Fakih (Economies, 2022)
This paper uses a unique dataset from Lebanon, a developing country with unstable political conditions, to explore the drivers of research outcomes. We use the Negative Binomial model to empirically examine the determinants of the total number of publications and single and co-authored articles. The results indicate that males are more likely to publish co-authored papers than females. Moreover, our findings show a quadratic relationship between age and the number of published papers with a peak at the age of 40. After this turning point, the publication rate starts to decrease at an increasing rate. When we run the model by gender, we find that females in large departments tend to publish more co-authored papers. We also find that full professors tend to publish more papers in Q1 and Q2 journals, while associate professors have more papers in Q2 and Q3 journals.
Keywords: 330; Lebanon; publications; research productivity